If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 + 7c = 22 Solving 1 + 7c = 22 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 7c = 22 + -1 Combine like terms: 1 + -1 = 0 0 + 7c = 22 + -1 7c = 22 + -1 Combine like terms: 22 + -1 = 21 7c = 21 Divide each side by '7'. c = 3 Simplifying c = 3
| -(d+5)-4=-2(d-6) | | 6X^2-100x-5000=0 | | 0.25-2x=5 | | 3(16)-3(-5)= | | 13s-13=2s-9 | | 0=5t^2+19.5t | | 7(-4+4a)=4(5+4a) | | x-50=17-5n | | 3(4x+1)-3x+15=0 | | k-6=13 | | 17x=51y+68# | | a+10=-4 | | 5x-45y=-15 | | 56=7n+99 | | 26=5x-14-x | | 6-1=97 | | -2x-5x=49 | | 5x^2+3=-8x | | .25x-6=2 | | 0.75y=4.875 | | 8=2s-12 | | 3(4x-5)=-7(-2x+3) | | 43=8x | | 2c=4c-16 | | -6(n-8)=4(12-5n) | | -7+x=-8minusx | | 8x+20x+8=12x | | 8-2n=17+n | | x-12+49=90 | | 3x+4xy+5= | | 7+3h=12+1h | | -12+40x=40x-60 |